Numust.style’s business innovation strategies using SWOT analysis and the canvas business models - Nur Solehah; Fanji Wijaya; Dadan Abdul Aaziz Mubarok (Institute of Computer Science (IOCS), 2023)
This research was conducted to formulate a strategy of business development and innovation Numust.style using Business Model Canvas (BMC) and SWOT analysis in the face of business competition. The data collection process was carried out through a live interview with the owner of Numust.style. The result found in this study that proved that numus.style already had a frame for work of nine elements of the Business Model Canvas or (BMC) and SWOT analysis that were the references to running a business, but there were still shortcomings in optimizing BMC and SWOT analysis for it, then the researchers adopted SWOT analysts (Strengths, Weaknesses, Opportunities, and Threats) to improve business development and innovation strategies. Numustic.style will optimize the use of strategies to enhance business development by making products a trendsetter or product that is bestseller or booming, as well as reviving creative ideas and innovations that will be implemented in business development strategies on a regular basis, in the development of business. as well as creating the best service for buyers who shop at numust.style.